MAIN CAUSES OF TRANSTIBIAL AMPUTATION IN REHABILITATION CENTER COLLEGE OF ASSISI GURGACZ: EPIDEMIOLOGICAL STUDY. (Fiep Bulletin - online, 2013)
Introduction: Amputation means the removal of all or part of a limb or more, which can be surgical or traumatic. Have a transtibial amputation can be defined as tibiotarsal dislocation and knee joint, which can be divided into proximal, middle and distal. And may occur for various reasons such as, trauma, vascular processes, thrombosis, tumor, infection, congenital and rheumatoid arthritis. The primary objective of this study was to identify the main causes of transtibial amputations in patients at the Rehabilitation Center of Assisi School Gurgacz. Methodology: This is a field study, epidemiological data collection from secondary sources, quantitative character, and the research sample comprised 143 individuals, consisting of 28 females and 115 males, aged 06-80 years. Data were obtained through consultation of medical records of patients at the Rehabilitation Centre FAG in October 2012. Results: The etiology of amputation was 45% trauma, diabetes 29%, 13% thrombosis, osteomilite 3%, 3% infection 3% cancer, congenital 1%, 2% by vascular and 1% rheumatoid arthritis. The highest incidence of amputations was found among adults, 20-60 years, and the leading cause in this age group was also traumatic 53.84%. Regarding the cause of amputation and sex in women was the predominant cause of diabetes with 42.85%, and the leading cause in men with traumatic was 51.30%. Of these 143 patients only 6 underwent a second amputation. Conclusion: From these data, it was possible to identify the main causes of transtibial amputation physiotherapy enabling better target their actions regarding rehabilitation, and also showing the need for further research on the subject addressed.
Keywords: transtibial amputation; cause; physiotherapy